Ljubezenska pisma med teorijo in literaturo - Greber, Erika (Primerjalna književnost, 2006)
The Russian Formalists are generally perceived as having established a rigid theory discourse, thereby producing or extending the disciplinary division. However, as early as 1922/23 Viktor Shklovsky wrote his remarkable epistolary novel Zoo, which unites both discourses. Zoo reshapes the traditional epistolary novel in metafictional style and revitalizes it by blurring the borders between documentary and poetic epistolarity. The established view of Shklovsky's novel as an "attempt to put into practice the principles to which he adhered as a critic" repeats the division between the discourses and reconfirms the dubitable hierchy of theory over literature. A more adequate view is gained by the idea of hybridity. Object level and meta level, literature and criticism are being merged. One of the most intriguing aspects of Zoo is its new use of the "editing" paratexts that traditionally established the stable division between editor and correspondence and that arenow used to deconstruct hierarchies. These paratexts form, also by means oftheir visual design, some kind of "paraletters" and are part of an epistolary meta-dialogue. With regard to the notion of a "dialogue" between theory and literature, it is highly significant that Shklovsky chose the dialogic genre of the epistolary novel for his critifictional enterprise.
Keywords: Šklovskij, Viktor; roman v pismih; ruska književnost; Russian literature; literarna teorija; literary theory